ISOLATING PROPERTIES OF A BENTONITE BUFFER IN CONDITIONS OF AN UNDERGROUND REPOSITORY FOR HIGH-LEVEL RADIOACTIVE WASTES - Laverov N.P.; Omel'yanenko B.I.; Yudintsev S.V. (My University, 2004)
The use of a bentonite buffer as an engineered barrier is specified in many contemporary designs of deep-seated underground repositories for high-level radioactive wastes (HLW). Briquettes of compacted bentonite are placed between a canister with HLW and rock. The thickness of the bentonite buffer is from 0.3 to 1.3 m. The isolating properties of bentonite are manifested in its low water permeability, swelling, plasticity, high sorption capacity, and high montmorillonite content (more than 60%). When saturated with water, bentonite swells and seals fissures in host rocks. In order to provide maximal durability of canisters and minimal solubility of HLW, the composition of bentonites is specifically selected to ensure reducing low-alkaline properties of pore waters. Due to low water permeability, radionuclides can migrate through the buffer only by diffusion. If a canister ensures the isolation of radionuclides from groundwater for 1000 years, a bentonite buffer increases this term by at least one order of magnitude. Only poorly sorbed long-lived radionuclides (14C, 129I, 79Se, 135Cs, and 99Tc) can overcome a bentonite buffer, and only thousands of years after the failure of canisters. By the time of such failure, all short- and mid-lived radionuclides (137Cs and 90Sr) will decay, and 98% of HLW radioactivity will be caused by actinides. The bentonite buffer is capable of retaining these most environmentally hazardous radionuclides for a virtually unlimited period. The transfer of radioisotopes in colloidal form through the buffer is completely excluded due to the very fine size of pores in bentonite and the lack of open channels. In underground repositories of vitrified HLW, 79Se and 135Cs can overcome a bentonite buffer only after 10000 years, and 99Tc, only after 300000 years.